Rare earth doped zirconium-titanium-cobalt hydrogen storage material and preparation method thereof

By doping Zr0.8Ti0.2Co alloy with rare earth elements Y or Ce, more hydrogen atom transport channels are formed and the microstructure is optimized, which solves the problems of difficulty in activation, easy disproportionation, low hydrogen storage capacity and insufficient cycle stability of ZrCo alloy, and achieves high-efficiency hydrogen storage performance.

CN120400650APending Publication Date: 2025-08-01南宁桂电电子科技研究院有限公司

Patent Information

Application Number
CN202510352545.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

In actual applications, existing ZrCo alloys have problems such as harsh activation conditions, easy disproportionation reaction, reduced hydrogen storage capacity and insufficient cycle stability, making it difficult to take into account both the disproportionation resistance and hydrogen storage properties.

Method used

The rare earth element Y or Ce doped Zr0.8Ti0.2Co alloy is used to form more hydrogen atom transport channels through grain boundaries and second phase regulation, optimize the microstructure and electronic structure, and improve the dynamic performance of hydrogen absorption and discharge.

Benefits of technology

Rare-earth element-doped ZrTiCo alloy significantly improves hydrogen storage capacity and hydrogen absorption rate, shortens the activation cycle, enhances cycling stability, and is suitable for large-scale manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120400650A_ABST
    Figure CN120400650A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth doped zirconium titanium cobalt hydrogen storage material and a preparation method thereof, the chemical general formula of the zirconium titanium cobalt hydrogen storage material is Zr < 0.8 > Ti < 0.2-x > M < x > Co, x is 0-0.05, and M is a rare earth element of which the atomic radius is greater than that of Ti; the preparation method comprises the following steps: sequentially carrying out mixed smelting, crushing and grinding, vacuum treatment and activating treatment on the raw materials to obtain the hydrogen storage material. Rare earth elements are doped in the Zr0. 8Ti0. 2Co alloy, more hydrogen atom transmission channels are triggered through grain boundary and second phase regulation and control, and the diffusion speed of hydrogen atoms can be increased. The doped rare earth element can also reduce hydrogen atom adsorption energy and dehydrogenation performance energy barriers and improve hydrogen absorption and desorption kinetics, meanwhile, the rare earth element can also increase adsorption sites of hydrogen atoms, the hydrogen storage capacity is further improved, and the rare earth element can further optimize the microstructure of the hydrogen storage alloy and regulate and control the electronic structure so as to optimize the kinetics performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and particularly to a rare earth-doped zirconium-titanium-cobalt hydrogen storage material and a preparation method thereof. Background Art

[0002] With the continuous increase in the demand for renewable resources, hydrogen energy, as a renewable energy source with great potential, is widely used in fields such as aerospace, battery manufacturing, hydrogen power generation, and energy-driven vehicles. ZrCo-based alloys are widely used in the storage, supply, and recovery processes of hydrogen isotopes due to their potential hydrogen storage capacity and are regarded as a potential material that can replace uranium. Compared with uranium, ZrCo alloys have the characteristics of no radiation, not easily catching fire, and strong helium-solidifying ability. Their hydrogen absorption capacity is about 1.9 wt%, and the pressure of the hydrogen absorption plateau is about 10 -3 pa. However, ZrCo still has certain problems in practical applications. First, the activation conditions of ZrCo alloys are relatively harsh and it is not easy to activate. Second, ZrCo alloys are prone to disproportionation reactions during multiple hydrogen absorption / desorption cycles or in high-temperature environments, generating a ZrC02 phase that does not absorb hydrogen and a ZrH2 phase that is difficult to desorb hydrogen, which leads to a reduction in hydrogen storage capacity and thus limits its further development and application. At the same time, the cycle stability and anti-poisoning performance of ZrCo alloys also need to be further improved.

[0003] In recent years, in order to overcome the above-mentioned problems, research has focused on aspects such as element doping, surface improvement, and preparation process optimization. Among many methods, the application of element doping is particularly common. As a typical AB-type hydrogen storage material, the performance optimization of ZrCo alloy often depends on doping different elements. At the A end, substitution elements such as Ti, Hf, Nb, etc. are widely used; while at the B end, substitution elements include Ni, Fe, Mn, Cu, Mo, etc. According to existing research data, when Ti element is doped into ZrCo alloy, the high-temperature anti-disproportionation performance is significantly improved, but the hydrogen absorption kinetics decreases. When Hf element is doped into ZrCo alloy, the anti-disproportionation performance is improved, but the price of Hf is relatively expensive. When Nb element is doped into ZrCo alloy to replace Zr, the initial activation performance is improved, but the maximum hydrogen absorption capacity decreases (Journal of Alloys and Compounds 784(2019)1062-1070). After Fe and Ni replace Co respectively, there is a controversy about the anti-disproportionation ability. After Al replaces Co, the cycle stability is enhanced, but the hydrogen absorption capacity decreases from 1.91wt% to 1.67wt.%. After Mo replaces Co, the initial activation time is shortened, and the hydrogen absorption capacity decreases from 1.89wt% to 1.66wt.%. After Pd replaces Co, the cycle stability is improved, but the maximum hydrogen absorption capacity decreases, and at the same time, the price of Pd is relatively expensive. Through the above analysis, element substitution is an important means to improve ZrCo hydrogen storage isotopes. Element substitution at the A end is more obvious for improving the thermodynamic performance of ZrCo, and substitution at the B end is more important for improving the kinetic performance of ZrCo alloy. However, the currently reported schemes all have certain limitations. There is an urgent need to find a solution that can improve both the anti-disproportionation performance and the hydrogen storage kinetics of the alloy hydrogen storage material. Summary of the Invention

[0004] The object of the present invention is to provide a rare earth-doped zirconium-titanium-cobalt hydrogen storage material and its preparation method to solve the problem that the above-mentioned ZrCo alloy material cannot take into account both the anti-disproportionation performance and the hydrogen storage performance.

[0005] To achieve the above object, in the first aspect of the present invention, a rare earth-doped zirconium-titanium-cobalt hydrogen storage material is provided. The chemical general formula of the zirconium-titanium-cobalt hydrogen storage material is: Zr 0.8 Ti 0.2-x M x Co, where x is 0 to 0.05, and M is a rare earth element with an atomic radius larger than that of Ti.

[0006] Zr 0.8 Ti 0.2The Co alloy ingot exhibits excellent anti-disproportionation characteristics when the Ti content reaches 20 mol% of the total content of Zr and Ti. Especially after a disproportionation treatment lasting up to 10 hours, the hydrogen pressure of the alloy remains almost unchanged, showing remarkable stability. However, the hydrogen absorption rate is not good. Therefore, in the prior art, Zr 0.8 Ti 0.2 Although the Co alloy demonstrates excellent anti-disproportionation performance, its hydrogen absorption kinetics is not satisfactory, and the doping modification of ZrCo-based alloys with rare earth elements has not been reported. Based on the characteristics of rare earth elements, the present invention is committed to deeply exploring the potential enhancement effect of the addition of elements such as Y and Ce on the hydrogen storage capacity of ZrTiCo alloys, in order to provide new ideas and directions for the research and application of hydrogen storage materials. The present invention dopes rare earth elements in the Zr 0.8 Ti 0.2 Co alloy, and more hydrogen atom transmission channels are induced through grain boundary and second-phase regulation, which is beneficial to improving the diffusion rate of hydrogen atoms. The doping of rare earth elements in the present invention can reduce the hydrogen atom adsorption energy and the energy barrier of dehydrogenation performance, improve the hydrogen absorption and desorption kinetics. At the same time, rare earth elements can increase the adsorption sites of hydrogen atoms, further improving the hydrogen storage capacity. Rare earth elements can optimize the microstructure of the hydrogen storage alloy and regulate the electronic structure, thereby optimizing the kinetic performance.

[0007] Preferably, x is 0.01 - 0.05.

[0008] Preferably, M is at least one of Y and Ce.

[0009] When M is Y, the atomic radius of the Y element is larger than that of the Ti element. As the content of the Y element increases, the lattice constant and the unit cell volume also increase, providing more effective hydrogen storage sites, which is beneficial to the improvement of the hydrogen storage capacity. Y atoms are prone to produce a grain boundary precipitation effect in the microstructure, providing more diffusion channels for hydrogen atoms and improving the hydrogen absorption kinetic characteristics.

[0010] When M is Ce, the atomic radius of the Ce element is larger than that of the Ti element. After Ce slightly replaces Ti, the lattice constant and the unit cell volume also increase, providing more effective hydrogen storage sites, which is beneficial to the improvement of the hydrogen storage capacity. The substitution of the Ce element helps to form a second phase distributed in a network shape, and the second phase distributed in a network shape helps to catalyze the more rapid dissociation and diffusion reaction of hydrogen molecules, improving the hydrogen absorption kinetic characteristics. However, when too much Ce element replaces Ti, a CeCo2 heterogeneous phase will be formed, reducing the hydrogen absorption amount and the cycle stability.

[0011] Generally speaking, the substitution of an appropriate content of rare earth elements can improve the maximum hydrogen absorption amount, hydrogen absorption kinetics, and cycle stability of the ZrTiCo hydrogen storage alloy.

[0012] The second aspect of the present invention provides a preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material, including the following steps:

[0013] (1) Add metal raw materials with a purity greater than 99.9% into a smelting furnace according to the stoichiometric ratio of Zr 0.8 Ti 0.2-x M x Co for smelting;

[0014] (2) Crush and grind the ingot obtained after smelting to obtain alloy powder;

[0015] (3) Tightly wrap the alloy powder with a nickel mesh, and then place it in a stainless steel container for vacuum treatment;

[0016] (4) After vacuum treatment, place the alloy powder in hydrogen for activation treatment until the alloy powder reaches the hydrogen absorption saturation state to obtain the zirconium-titanium-cobalt hydrogen storage material.

[0017] Preferably, in step (1), the smelting process is: in a helium environment, use an arc melting furnace in a water-cooled copper furnace for smelting.

[0018] Preferably, in step (1), in order to ensure uniform distribution of metal elements, turn over and remelt the ingot after smelting more than three times.

[0019] Preferably, in step (2), the particle size of the alloy powder is 200-300 mesh.

[0020] Preferably, in step (2), the crushing is carried out by manual crushing method, and the grinding combines rough grinding with a stainless steel mortar and fine grinding with an agate mortar.

[0021] Preferably, in step (2), after the obtained alloy ingot undergoes surface treatment, it is polished with a fine grinding wheel to remove the oxide film, and further cut into small pieces with a vise for subsequent treatment.

[0022] Preferably, in step (2), a conductive type hot embedding material is used to embed these small pieces at a temperature of about 130 °C to enhance their stability and operability for further experimental analysis.

[0023] Preferably, in step (3), the temperature of the vacuum treatment is 180-220 °C, and the time is 1-3 h.

[0024] The purpose of the vacuum treatment in the present invention is to remove various gas impurities attached to the surface of the alloy.

[0025] Preferably, in step (4), the temperature of the activation treatment is 200-300 °C, the time is 0.5-2 h, and the pressure of hydrogen is 1-5 MPa.

[0026] Preferably, in step (4), in order to ensure the purity of the zirconium-titanium-cobalt hydrogen storage material and prevent oxidation, the prepared zirconium-titanium-cobalt hydrogen storage material is stored in a glass bottle containing absolute ethanol.

[0027] Therefore, the present invention adopts the above-mentioned rare-earth-doped zirconium-titanium-cobalt hydrogen storage material and its preparation method, and has the following beneficial effects:

[0028] (1) By combining formula optimization and microstructure improvement, the present invention alloyizes with rare-earth element M and transition metals Zr, Ti, and Co, reduces the activation conditions of the ZrCo alloy, shortens the activation period, improves its microstructure, overcomes the problem of poor hydrogen absorption kinetics of the ZrCo-based hydrogen storage alloy, makes its advantages appear, and significantly improves the hydrogen absorption and desorption performance of the alloy.

[0029] (2) The Zr 0.8 Ti 0.2-x M x Co hydrogen storage material prepared by the present invention is easy to activate, has a high hydrogen storage capacity, and good hydrogen absorption and desorption performance.

[0030] (3) The atomic radii of rare-earth elements Y and Ce in the present invention are larger than that of the Ti element. The rare-earth elements replace the titanium element, and the lattice parameter increases, which is beneficial to increasing more hydrogen storage sites and improving the maximum hydrogen storage capacity of the ZrTiCo alloy.

[0031] (4) The addition of rare-earth elements in the present invention accelerates the hydrogen absorption kinetics of the alloy. The rare-earth element Y forms a grain boundary precipitation phenomenon, providing more effective paths for hydrogen atom diffusion; the oxide phase of the rare-earth element Ce forms a network structure, which has a catalytic effect on the dissociation and diffusion of hydrogen atoms. Hydrogen diffusion is very active, significantly shortening the incubation period, quickly activating the alloy, and the catalytic effect of the newly formed phase also significantly improves the hydrogen absorption performance and hydrogen absorption speed of the alloy, which provides strong support for the optimization of the kinetic performance of the ZrTiCo alloy in the prior art.

[0032] (5) In the process of crushing and grinding, the present invention adopts a method of manual crushing combined with rough grinding in a stainless-steel mortar and fine grinding in an agate mortar, forming a large number of crystal defects, increasing the nucleation points and diffusion channels of hydrogen, further reducing the thermal stability of the hydride and improving the hydrogen absorption and desorption kinetic performance of the alloy.

[0033] (6) The hydrogen storage alloy preparation method provided by the present invention has easily available raw materials, common equipment, relatively mild process conditions, simple operation, short preparation time, and is suitable for large-scale manufacturing and wide promotion.

[0034] The technical solution of the present invention will be further described in detail below through the drawings and embodiments. Description of the Drawings

[0035] Figure 1 XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 1-3;

[0036] Figure 2 SEM images of the hydrogen storage materials of Comparative Example 1 and Example 2;

[0037] Figure 3 EDS spectrum of the hydrogen storage material of Example 2;

[0038] Figure 4 XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 4-6;

[0039] Figure 5 SEM images of the hydrogen storage materials of Examples 4-6;

[0040] Figure 6 EDS spectrum of the hydrogen storage material of Example 4;

[0041] Figure 7 Initial activation kinetic curves of the hydrogen storage materials of Comparative Example 1 and Examples 1-3;

[0042] Figure 8 Initial activation kinetic curves of the hydrogen storage materials of Comparative Example 1 and Examples 4-6;

[0043] Figure 9 XRD patterns of the corresponding hydrides of the hydrogen storage materials of Comparative Example 1 and Examples 1-3;

[0044] Figure 10 XRD patterns of the corresponding hydrides of the hydrogen storage materials of Comparative Example 1 and Examples 4-6;

[0045] Figure 11 Cycling stability curves of the hydrogen storage materials of Comparative Example 1 and Examples 1-3;

[0046] Figure 12 Cycling stability curves of the hydrogen storage materials of Comparative Example 1 and Examples 4-6;

[0047] Figure 13 XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 1-3 after 10 cycles of hydrogen absorption and desorption;

[0048] Figure 14 XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 4-6 after 10 cycles of hydrogen absorption and desorption. Detailed implementation manners

[0049] The present invention will be further described below. It should be noted that this embodiment is based on the present technical solution, and detailed implementation manners and specific operation procedures are given, but the present invention is not limited to this embodiment.

[0050] Comparative Example 1

[0051] A preparation method of a Zr 0.8 Ti 0.2 Co hydrogen storage material, comprising the following steps:

[0052] (1) Accurately weigh high-purity metal raw materials (Zr, Ti, Co) with a purity exceeding 99.9% according to the molar ratio Zr∶Ti∶Co = 0.8∶0.20∶1, and then perform arc melting operation in a water-cooled copper crucible to ensure obtaining an alloy ingot with uniform mixing of the metal raw materials.

[0053] To further ensure the uniform distribution of components in the alloy ingot, the alloy ingot was flipped at least six times during the melting process to ensure more uniform mixing effect.

[0054] After the obtained alloy ingot undergoes surface treatment, it is polished with a fine grinding wheel to remove the oxide film, and further cut into small pieces with a vise. A part of the alloy sample is selected as the object for subsequent embedding treatment for further experimental analysis; while another part of the alloy sample is coarsely ground through a stainless steel mortar and finely ground through an agate mortar, and finally an alloy powder with a particle size range of 200 - 300 mesh is obtained, providing necessary sample preparation for subsequent performance testing and characterization. This step helps to enhance the surface quality of the alloy and provides suitable samples for the following experiments.

[0055] (2) Tightly wrap the alloy powder with a nickel mesh, then place it in a stainless steel container, and perform vacuum treatment at a temperature of 200 °C for 2 hours to remove various gas impurities attached to the surface of the alloy.

[0056] (3) After vacuum treatment, activate the alloy powder under a hydrogen pressure of 250 °C for 1 hour to ensure it reaches the hydrogen absorption saturation state.

[0057] Example 1

[0058] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Y x Co, x = 0.01, and the preparation method and testing method of the hydrogen storage material are the same as those in Comparative Example 1.

[0059] Example 2

[0060] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Y xCo, with x = 0.03, the preparation method and testing process of the hydrogen storage material are the same as those in Comparative Example 1.

[0061] Example 3

[0062] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Y x Co, with x = 0.05, the preparation method and testing process of the hydrogen storage material are the same as those in Comparative Example 1.

[0063] Example 4

[0064] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Ce x Co, with x = 0.01, the preparation method and testing process of the hydrogen storage material are the same as those in Comparative Example 1.

[0065] Example 5

[0066] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Ce x Co, with x = 0.03, the preparation method and testing process of the hydrogen storage material are the same as those in Comparative Example 1.

[0067] Example 6

[0068] The difference between this example and Comparative Example 1 is that the chemical general formula of the hydrogen storage material is different. The chemical general formula of the hydrogen storage material in this example is Zr 0.8 Ti 0.2-x Ce x Co, with x = 0.05, the preparation method and testing process of the hydrogen storage material are the same as those in Comparative Example 1.

[0069] Test Example

[0070] (1) Perform XRD, SEM, and EDS characterizations on the alloy hydrogen storage materials prepared in the examples and comparative examples.

[0071] Figure 1XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 1 to 3 are shown. As can be seen from the figure, the structure of the hydrogen storage material prepared in Comparative Example 1 is the cubic ZrCo main phase, and no other secondary phase is observed; the structure of the hydrogen storage material prepared in Example 1 is the cubic ZrCo main phase, and no other secondary phase is observed. The phase is basically the same as that of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The unit cell parameters of Example 1 are slightly larger than those of Comparative Example 1. The atomic radius of Y is larger than that of Ti. After Y partially replaces Ti, the unit cell volume increases; the structure of the hydrogen storage material prepared in Example 2 is the cubic ZrCo main phase, and no other secondary phase is observed. The phase is basically the same as that of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The unit cell parameters of Example 2 are slightly larger than those of Example 1, which proves that as the doping amount of Y atoms increases, the unit cell volume increases; the structure of the hydrogen storage material prepared in Example 3 is the cubic ZrCo main phase, and no other secondary phase is observed. The phase is basically the same as that of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The unit cell parameters of Example 3 are slightly larger than those of Example 2, which proves that as the doping amount of Y atoms increases, the unit cell volume increases.

[0072] Table 1 List of unit cell parameters of the hydrogen storage materials of the examples and comparative examples

[0073]

[0074]

[0075] Figure 2 SEM images of the hydrogen storage materials prepared in Comparative Example 1 and Example 2 are shown. From Figure 2 the images, it can be seen that the SEM image of the hydrogen storage material in Comparative Example 1 shows a single main phase, and no obvious secondary phase exists, which is consistent with the XRD results; the SEM image of the hydrogen storage material in Example 2 shows that after the rare earth element doped with Ti element, a certain phenomenon of grain boundary precipitation appears.

[0076] Figure 3 EDS image of the hydrogen storage material prepared in Example 2 is shown. From Figure 3 the image, it can be seen that the main component of the grain boundary precipitation is Y element. Since the atomic radius of Y is relatively large and exceeds the maximum solid solubility of the main phase, grain boundary segregation occurs.

[0077] Figure 4 XRD patterns of the hydrogen storage materials of Comparative Example 1 and Examples 4 to 6 are shown. From Figure 4It can be seen that the structures of the hydrogen storage materials prepared in Examples 4 to 6 are all cubic ZrCo matrix phases, and at the same time, the CeO2 secondary phase is observed. This is because Ce is prone to absorbing oxygen during the melting process, resulting in oxidation. The refinement results are shown in Table 1. The unit cell parameters of the hydrogen storage materials in Examples 4 to 6 are slightly increased compared to Comparative Example 1. Since the atomic radius of Ce is larger than that of Ti, after Ce partially replaces Ti, the unit cell volume increases.

[0078] Figure 5 SEM images of the hydrogen storage materials prepared in Examples 4 to 6 Figure 5 Among them, (a), (b), and (c) are the hydrogen storage materials prepared in Example 4, Example 5, and Example 6 respectively. From Figure 5 It can be seen that there are tiny white phase precipitates in the hydrogen storage material of Example 4, which is consistent with the CeO2 secondary phase corresponding to XRD; there are tiny white phase precipitates in the hydrogen storage material of Example 5, and the white phases are intertwined into a network structure, which is consistent with the CeO2 secondary phase corresponding to XRD. The network secondary phase structure can provide a diffusion transport channel for hydrogen atoms, which helps to improve the hydrogen absorption kinetics characteristics; there are white phases intertwined into a network structure in the hydrogen storage material of Example 6, which is consistent with the CeO2 secondary phase corresponding to XRD, and at the same time, uneven dark phases appear, which are CeCo2 phases.

[0079] Figure 6 EDS diagram of Example 4. From Figure 6 It can be seen that the main precipitation at the grain boundaries is CeO2. Since the atomic radius of Ce is relatively large and exceeds the maximum solid solubility of the matrix phase, grain boundary segregation occurs.

[0080] (2) The hydrogen absorption and desorption performance of the alloy hydrogen storage materials prepared in the examples and comparative examples was tested.

[0081] In order to accurately evaluate the performance of the alloy during the hydrogen absorption / desorption cycle, the alloy samples were specifically subjected to hydrogen absorption treatment under preset temperature and hydrogen pressure conditions. Subsequently, these alloy samples were placed in a dynamic vacuum environment for dehydrogenation operation. During the hydrogen absorption stage, the temperature was controlled at 250 °C and carried out under a hydrogen pressure of 2 MPa (the specific hydrogen pressure depends on the experimental requirements). The dehydrogenation stage was carried out by dynamic evacuation at a temperature of 400 °C. The above operations were repeated during the hydrogen absorption and desorption cycle.

[0082] Figure 7 Initial activation kinetic curves of the hydrogen storage materials of Comparative Example 1 and Examples 1 to 3. From Figure 7As can be seen from Table 2, the hydrogen storage material of Comparative Example 1 was hydrogenated at 2 MPa and 250 °C to reach the maximum hydrogen absorption capacity of 1.708 wt%, and the time required to reach 90% of the maximum hydrogen absorption capacity was 2379 s; the hydrogen storage material of Example 1 was hydrogenated at 2 MPa and 250 °C to reach the maximum hydrogen absorption capacity of 1.852 wt%. The addition of rare earth elements increased the unit cell volume, which could provide more tetrahedral and octahedral active sites for hydrogen atom storage. Therefore, the hydrogen absorption capacity was improved compared with that of Comparative Example 1. The time required for Example 1 to reach 90% of the maximum hydrogen absorption capacity was 290 s, and the hydrogen absorption rate was increased by about 7 times compared with that of Comparative Example 1. The hydrogen absorption kinetics was significantly improved after the addition of rare earth elements. The doping of Y significantly improved the hydrogen absorption rate and hydrogen absorption capacity of the alloy and shortened the incubation period of hydrogen absorption; the hydrogen storage material of Example 2 was hydrogenated at 2 MPa and 250 °C to reach the maximum hydrogen absorption capacity of 1.935 wt%. The time required for Example 1 to reach 90% of the maximum hydrogen absorption capacity was 123 s, and the hydrogen absorption rate was further improved compared with that of Example 1. The hydrogen absorption kinetics was significantly improved after the addition of rare earth elements. The grain boundary effect constructed by the Y doping method could provide more diffusion paths for hydrogen atom diffusion, significantly improving the hydrogen absorption rate and hydrogen absorption capacity of the alloy; the hydrogen storage material of Example 3 was hydrogenated at 2 MPa and 250 °C to reach the maximum hydrogen absorption capacity of 1.922 wt%. The hydrogen absorption capacity was improved compared with that of Comparative Example 1, but with the further increase of the Y element, the hydrogen absorption capacity decreased. Due to the limited solid solubility of the BCC matrix phase, the excessive Y atoms exceeded the solid solubility limit, so the Y segregation phenomenon occurred. The segregation phase and the increased grain boundary effect reduced the hydrogen storage capacity. The time required for the hydrogen storage material of Example 3 to reach 90% of the maximum hydrogen absorption capacity was 65 s, and the hydrogen absorption rate was further improved compared with that of Comparative Example 1. The hydrogen absorption kinetics was significantly improved after the addition of rare earth elements. The grain boundary effect constructed by the Y doping method could provide more diffusion paths for hydrogen atom diffusion, significantly improving the hydrogen absorption rate and hydrogen absorption capacity of the alloy and shortening the incubation period of hydrogen absorption.

[0083] Figure 8 Figure 4 shows the initial kinetic curves of the hydrogen storage materials prepared in Comparative Example 1 and Examples 4-6. From Figure 8As can be seen from Table 2, the hydrogen storage material of Example 4 absorbs hydrogen under the conditions of 2 MPa and 250 °C, reaching a maximum hydrogen absorption capacity of 1.913 wt%. The addition of rare earth element Ce increases the unit cell volume, which can provide more tetrahedral and octahedral active sites for hydrogen atom storage. Therefore, the hydrogen absorption capacity is improved compared to Comparative Example 1. The time required for Example 4 to reach 90% of the maximum hydrogen absorption capacity is 190 s, and the hydrogen absorption rate is increased by about 12 times compared to Comparative Example 1. After the addition of rare earth element Ce, the hydrogen absorption kinetics is significantly improved. The doping of Ce significantly improves the hydrogen absorption rate and hydrogen absorption capacity of the alloy, and shortens the incubation period of hydrogen absorption; the hydrogen storage material of Example 5 absorbs hydrogen under the conditions of 2 MPa and 250 °C, reaching a maximum hydrogen absorption capacity of 1.935 wt%. The addition of rare earth element Ce increases the unit cell volume, which can provide more tetrahedral and octahedral active sites for hydrogen atom storage. Therefore, the hydrogen absorption capacity is improved compared to Comparative Example 1. The time required for Example 5 to reach 90% of the maximum hydrogen absorption capacity is 72 s, which is further improved compared to Example 4. After the addition of rare earth element Ce, the hydrogen absorption kinetics is significantly improved. The second phase with a network structure provides more diffusion channels for hydrogen atoms. At the same time, rare earth Ce has a strong catalytic effect and a strong affinity for hydrogen atoms. The doping of Ce significantly improves the hydrogen absorption rate and hydrogen absorption capacity of the alloy, and shortens the incubation period of hydrogen absorption; the hydrogen storage material of Example 6 absorbs hydrogen under the conditions of 2 MPa and 250 °C, reaching a maximum hydrogen absorption capacity of 1.785 wt%. The maximum hydrogen storage capacity of Example 6 is lower than that of Example 5, which may be caused by CeCo2 that does not absorb hydrogen. The time required for Example 6 to reach 90% of the maximum hydrogen absorption capacity is 37 s, which is further improved compared to Example 5. After the addition of rare earth element Ce, the hydrogen absorption kinetics is significantly improved. The second phase with a network structure provides more diffusion channels for hydrogen atoms. At the same time, rare earth Ce has a strong catalytic effect and a strong affinity for hydrogen atoms. The doping of Ce significantly improves the hydrogen absorption rate and hydrogen absorption capacity of the alloy, and shortens the incubation period of hydrogen absorption.

[0084] Table 2 Test results of hydrogen storage performance of comparative examples and examples

[0085]

[0086]

[0087] After the hydrogenation is completed, the hydrogen storage materials of the examples and comparative examples are characterized by XRD. Figure 9 XRD patterns of the corresponding hydrides of the hydrogen storage materials of Comparative Example 1 and Examples 1 to 3 are shown. As can be seen from Figure 9 it that the hydrides of Comparative Example 1 and Examples 1 to 3 are all ZrCoH3 hydrides. Figure 10 XRD patterns of the corresponding hydrides of the hydrogen storage materials of Comparative Example 1 and Examples 4 to 6 are shown. As can be seen from Figure 10 it that the hydrides of Examples 4 to 6 are also all ZrCoH3 hydrides.

[0088] The hydrogen storage materials of the comparative examples and the examples were subjected to hydrogen absorption and desorption cycle tests. Figure 11 Figure 1 shows the hydrogen absorption and desorption cycle test results of the hydrogen storage materials of Comparative Example 1 and Examples 1-3. Figure 11 As can be seen from it, after 10 cycles of hydrogen absorption and desorption of the hydrogen storage material of Comparative Example 1, the hydrogen storage capacity retention rate was 87.77%; after 10 cycles of hydrogen absorption and desorption of the hydrogen storage materials of Examples 1-3, the hydrogen storage capacity retention rates were 90.27%, 88.94%, and 88.23% respectively. Figure 12 Figure 2 shows the hydrogen absorption and desorption cycle test results of the hydrogen storage materials of Comparative Example 1 and Examples 4-6. Figure 12 As can be seen from it, after 10 cycles of hydrogen absorption and desorption of the hydrogen storage materials of Examples 4-6, the hydrogen storage capacity retention rates were 92.43%, 92.44%, and 84.2% respectively. The hydrogen storage capacity retention rate of Example 6 decreased slightly compared with that of Comparative Example 1. This may be due to the presence of the second phase CeCo2, which reduced the alloy cycle stability. Generally speaking, the doping of rare earth Y and Ce in ZrTiCo-based alloys has achieved good results in improving the hydrogen absorption amount and hydrogen absorption kinetics.

[0089] The products after the hydrogen absorption and desorption cycle tests of the comparative examples and the examples were analyzed by XRD. Figure 13 Figure 3 shows the XRD patterns of the products after the hydrogen absorption and desorption cycle tests of Comparative Example 1 and Examples 1-3. Figure 13 As can be seen from it, the main phase of the hydrogen storage material of Comparative Example 1 was still the BCC structure main phase, showing good structural stability; the main phases of the products of Examples 1-3 were still the BCC structure main phases, showing good structural stability, fully proving an effective way to modify the hydrogen storage performance of rare earth-doped ZrTiCo alloys, which can achieve an increase in the maximum hydrogen absorption amount and hydrogen absorption rate while ensuring better cycle stability. Figure 14 Figure 4 shows the XRD patterns of the products after the hydrogen absorption and desorption cycle tests of Comparative Example 1 and Examples 4-6. Figure 14 As can be seen from it, the main phases of the products of Examples 4-6 were still the BCC structure main phases, also showing good structural stability.

[0090] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that they can still modify or equivalently replace the technical solutions of the present invention, and these modifications or equivalent replacements cannot make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A rare earth-doped zirconium-titanium-cobalt hydrogen storage material, characterized in that: The chemical general formula of the zirconium-titanium-cobalt hydrogen storage material is: Zr 0.8 Ti 0.2-x M x Co, where x is 0 to 0.05 and M is a rare earth element with an atomic radius larger than that of Ti.

2. The rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 1, characterized in that: x is from 0.01 to 0.

05.

3. A rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 1, characterized in that: M is at least one of Y and Ce.

4. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) Add metal raw materials with a purity greater than 99.9% into a melting furnace for melting according to the stoichiometric ratio of Zr 0.8 Ti 0.2-x M x Co; (2) Crush and grind the ingot obtained after melting to obtain alloy powder; (3) Tightly wrap the alloy powder with a nickel mesh, and then place it in a stainless steel container for vacuum treatment; (4) After vacuum treatment, place the alloy powder in hydrogen for activation treatment until the alloy powder reaches the hydrogen absorption saturation state to obtain the zirconium-titanium-cobalt hydrogen storage material.

5. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (1), the melting process is as follows: in a helium environment, use an arc melting furnace in a water-cooled copper furnace for melting.

6. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (1), in order to ensure uniform distribution of metal elements, turn over and remelt the ingot after melting more than three times.

7. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (2), the particle size of the alloy powder is 200-300 mesh.

8. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (3), the temperature of the vacuum treatment is 180-220 °C, and the time is 1-3 h.

9. The preparation method of a rare earth-doped zirconium titanium cobalt hydrogen storage material according to claim 4, characterized in that: In step (4), the temperature of the activation treatment is 200-300 °C, the time is 0.5-2 h, and the pressure of hydrogen is 1-5 MPa.

10. The preparation method of a rare earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (4), in order to ensure the purity of the zirconium-titanium-cobalt hydrogen storage material and prevent oxidation, store the prepared zirconium-titanium-cobalt hydrogen storage material in a glass bottle containing anhydrous ethanol.

Citation Information

Patent Citations

  • Hydrogen storage material doped with V and capable of improving performance of ZrCo hydrogen storage alloy and preparation method of hydrogen storage material

    CN112779439A

  • ZrCo hydrogen storage alloy material and preparation method and application thereof

    CN119571136A

  • Hydrogen storage alloy and nickel-hydrogen storage battery

    JP2011058082A

Cited By

  • Device and method for preparing titanium hydrogen storage alloy for solid hydrogen storage

    CN121163220A